Distributed power allocation schemes for precoded multicell MISO-OFDM systems - Silva, Adão
In this paper we propose distributed power allocation schemes for the downlink of distributed precoded multicell MISO-OFDM systems. The precoders are designed in two phases: first the precoder vectors are computed in a distributed manner at each BS considering two criteria, distributed zero-forcing and virtual signal-to-interference noise ratio; then the system is optimized through distributed power allocation with per-BS power constraint. The proposed power allocation schemes minimize the average virtual bit error rate over all user terminals and the available subcarriers. Both the precoder vectors and the power allocation are computed by assuming that the BSs have only knowledge of local channel state information. The performance of the proposed schemes are compared against other power allocation schemes that have been recently proposed for multicell systems.